Project S5 - Design with SolidWorks - Chang, Kuang-Hua (Design Theory and Methods Using CAD/CAE, 2015)
In Project S5, we introduce SolidWorks design optimization capabilities as well as conducting interactive design using the suite of SolidWorks CAD/CAE/CAM capabilities for a multidisciplinary design problem. We include an optimization design study for a cantilever beam as a single-objective optimization. Then we present a single-piston engine example to illustrate the interactive design process discussed in Chapter 3 involving multiple engineering disciplines. For those who are not familiar with SolidWorks and embedded CAE/CAM modules, we encourage you to go over Projects S1 to S4 of the book series before moving forward with this tutorial project. Without going over these prior projects, you may get lost very quickly. Example models are available for download at the book’s companion website.